La metafisica come antropodecentrismo - Biuso, Alberto Giovanni (Mechane, 2022)
The essay tries to grasp starting from Heidegger and beyond Heidegger, from Mazzarella and beyond Mazzarella, the anthropodecentric structure that constitutes the real reason for the fecundity and necessity of metaphysics. Human meaning, its history and its future are inseparable from the atomic, molecular, thermodynamic story of the cosmos. Metaphysics, πρώτη φιλοσοφία, is also this attempt to observe and understand the world from the point of view of matter, of the whole, of the Φύσις.